Cutting of oversized stone blocks using thermite mixture (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
To assess the applicability of thermite mixtures as a non-explosive technique for splitting oversize rock blocks. Bench tests on granite, diabase and dense limestone used localized high-temperature thermal loading to induce directional cracking. The approach delivered a high yield of saleable fragments (~70–75%) and reduced processing time (~20–25 min per block) compared to mechanical or hydraulic-wedge methods. We discuss fracture mechanisms under thermal gradients, limitations (rock moisture, surface preparation) and industrial safety. A practice-oriented evaluation outlining conditions under which thermite-based splitting is advantageous for hard rocks. The results of the work can be used in stone-mining quarries and stone-processing enterprises.
Keywords: oversize rock blocks; thermite mixture; non-explosive splitting; thermal cracking; directional fracture; hard rock; safety